2005
DOI: 10.1051/forest:2005009
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of increased deer browsing winter on silver fir and spruce regeneration in the Southern Vosges mountains: Implications for forest management

Abstract: -Forest and wildlife management practices in the Vosges have changed rapidly during the last 200 years, modifying interactions between animals and plants, especially deer and silver fir. In order to assess the impact of browsing on fir regeneration, we compared two sets of similar forests which differed primarily in terms of deer population dynamics and history. On slopes with southern exposures, many fir seedlings did not reach heights above 30 cm and spruce developed; this was related to browsing intensity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
4
30
1
2
Order By: Relevance
“…Different studies have outlined the importance of environmental conditions to finally determine herbivory intensity [25,46]. Although we did not find effects of fertilization treatments besides leaf N, it is likely that perturbations that modify nutrient availability, such as forest fires, can potentially modify leaf chemistry and affect herbivore performance.…”
Section: Discussioncontrasting
confidence: 46%
“…Different studies have outlined the importance of environmental conditions to finally determine herbivory intensity [25,46]. Although we did not find effects of fertilization treatments besides leaf N, it is likely that perturbations that modify nutrient availability, such as forest fires, can potentially modify leaf chemistry and affect herbivore performance.…”
Section: Discussioncontrasting
confidence: 46%
“…Very similar results of the impact of winter on large herbivores were reported in studies by Christianson and Creel (2007). In winter, the animals face a shortage of good-quality food and increased energy expenditure for thermoregulation and movement (Moen 1973;Parker et al 1996) and so they intensively exploit the shoots of woody species as the most attractive and often the only source of their food (Gill 1992;Heuze et al 2005;Hodder et al 2013). The winter supply of green cereal crops on agricultural lands was of higher quality than tree shoots in the forest environment but its quantity was too small to constitute a more significant component of large herbivore diet.…”
Section: Discussionsupporting
confidence: 66%
“…Ungulates can be the most important driver of meta-community structure in mesic systems without strong abiotic influences in warm temperate forests [28]. An analysis of the global level of browsing revealed that seedlings on south-facing slopes were browsed more intensively than those on slopes with other exposures [29]. Similarly, Cagnacci et al [30] showed that probability of roe deer (Capreolus capreolus L.) presence decreased nonlinearly with elevation because the thicker snow cover and lower temperatures in spring reduced ungulate movement and the duration of the period when seedlings are available.…”
Section: Introductionmentioning
confidence: 99%